Is the onset of septoria tritici blotch epidemics related to the local pool of ascospores?. (27th May 2015) - Morais, D.; Sache, I.; Suffert, F.; Laval, V.
Abstract : To elucidate the early epidemic stages of septoria tritici blotch, especially the relationship between the onset of epidemics, the local availability of primary inoculum, and the presence of wheat debris, the early disease dynamics and airborne concentration in Zymoseptoria tritici ascospores were concomitantly assessed at a small spatiotemporal scale and over two years, using spore traps coupled with a qPCR assay. One plot, with the crop debris left, provided a local source of primary inoculum, while the other plot, without debris, lacked any. According to the assay's limits of detection, daily spore trap samples were classified as not detectable or not quantifiable, detectable, and quantifiable. The proportions of samples assigned to the different classes and numbers of spores in samples classified as quantifiable were significantly different between years, time periods (from November to March) and spore trap location (field with or without debris). The effect of year on the airborne ascospore concentration was high: 22 daily peaks with more than 230 ascospores m −3  day −1 were identified in the autumn of 2012/13, but none in the autumn of 2011/12. The local presence of wheat debris had no obvious effect on the amount of airborne ascospores or on the earliness of the two epidemics, especially in the year with high inoculum pressure (2012/13). These results suggest that the amount of primary airborne inoculum available in a wheat crop is not a limiting factor for the onset of an epidemic.